Test Research on Airspring Damping Characteristics for Rail Vehicles - CHEN Can-hui; CHEN Wen-hai; CHENG Hai-tao; HUANG Tao; BU Ji-ling (机车电传动)
The paper discussed the airspring damping system theory analysis and test method. Through a series of damping test on airspring of rail vehicle, the damping coefficient factors of orifice diameter, amplitude, and vertical load were investigated and rules wereconcluded, which provided suggestions to bogies design.